Pediatric critical care nursing research priorities - Initiating international dialogue - Tume, L.; Coetzee, M.; Dryden-Palmer, K.; Hickey, P.; Kinney, S.; Latour, Jos; Pedreira, M.; Sefton, G.; Sorce, L.; Curley, M. (Lippincott Williams and Wilkins, 2015)
Objective: To identify and prioritize research questions of concern to the practice of pediatric critical care nursing practice. Design: One-day consensus conference. By using a conceptual framework by Benner et al describing domains of practice in critical care nursing, nine international nurse researchers presented state-of-the-art lectures. Each identified knowledge gaps in their assigned practice domain and then poised three research questions to fill that gap. Then, meeting participants prioritized the proposed research questions using an interactive multi-voting process. Setting: Seventh World Congress on Pediatric Intensive and Critical Care in Istanbul, Turkey. Participants: Pediatric critical care nurses and nurse scientists attending the open consensus meeting. Interventions: Systematic review, gap analysis, and interactive multi-voting. Measurements and Main Results: The participants prioritized 27 nursing research questions in nine content domains. The top four research questions were 1) identifying nursing interventions that directly impact the child and family’s experience during the withdrawal of life support, 2) evaluating the long-term psychosocial impact of a child’s critical illness on family outcomes, 3) articulating core nursing competencies that prevent unstable situations from deteriorating into crises, and 4) describing the level of nursing education and experience in pediatric critical care that has a protective effect on the mortality and morbidity of critically ill children. Conclusions: The consensus meeting was effective in organizing pediatric critical care nursing knowledge, identifying knowledge gaps and in prioritizing nursing research initiatives that could be used to advance nursing science across world regions.